Heavy + light chain analysis to assign myeloma response is analogous to the IMWG response criteria. Issue 3 (4th March 2018) - Fouquet, Guillemette; Snell, Kym IE; Guidez, Stéphanie; Schraen, Susanna; Boyle, Eileen; Renaud, Loïc; Desmier, Déborah; Machet, Antoine; Moya, Niels; Systchenko, Thomas; Gruchet, Cécile; Decaux, Olivier; et al.
Abstract: Automated serum heavy + light chain (HLC) immunoassays can measure the intact immunoglobulins of each light chain type separately. We though to compare HLC assays with electrophoretic techniques in determining International Myeloma Working Group (IMWG) response criteria. 114 myeloma patients from 2 trials were included. HLC measurements were made utilizing archived sera and response assessments compared with those based on electrophoretic analysis at the time of the trials. Assessments at ∼90 days and maximal response were compared as was the power of the 2 techniques for predicting later responses, overall survival, and progression. The kappa statistic indicated good agreement between the 2 methods for determining IMWG response criteria, although HLC measurements might give better predictions of subsequent responses and frequently gave an earlier indication of change. HLC measurements could represent an alternative to electrophoretic techniques in determining IMWG response. Validation with a greater range of patient responses is needed for confirmation.